Genotypes of Polymorphic Loci of BDNF and COMT Genes as Factors of Individual Differences in Coping Intelligence - E.V. Volkova; I.O. Kuvaeva; A.V. Varlamov; N.E. Volkova; D.A. Dokuchaev (Экспериментальная психология)
The study aims to clarify the role of the catechol-O-methyltransferase gene and the brain-derived neurotrophic factor gene in individual differences of coping intelligence. Coping intelligence is defined as a person's ability to productively resolve stressful situations while maintaining health potential and increasing the person's development potential. Variability of coping is considered as a manifestation of individual differences in coping intelligence. The study involved respondents aged 25 to 54 years (N=251; M=35.82; SD=9.50; 46% male). The Coping Questionnaire (ACS) adjusted for an adult sample was used. Evidence is provided for the reliability of the ACS questionnaire and the stability of the three-factor structure of coping styles for an adult sample. The BDNF genotype (rs6265) and the COMT genotype (rs4680) were identified at the Scientific Center for Molecular Genetic Research “DNKOM Laboratory”. The results obtained indicate a significant difference in the severity of unproductive coping “Tension Reduction” and “Distraction” coping depending on the COMT genotype: the highest in individuals with the G/A genotype, the least in individuals with the G/G genotype. The same frequency of using the copings “Tension Reduction” and “Distraction” is observed in people with the Val/Val and Val/Met genotypes of the BDNF gene, regardless of the genotypes of the COMT gene. But in the case of the Met/Met genotype of the rs6265 polymorphic locus of the BDNF gene, a so-called “splitting” is observed: an increase in unproductive copings “Tension Reduction” and “Distraction” in individuals with the G/A genotype of the rs4680 polymorphic locus of the COMT gene and a decrease these copings in individuals with the G/G genotype. No differences were found in relation to other coping measures, which requires the use of a wider range of genetic markers to describe individual differences in the manifestation of coping intelligence.